Soviet Jews in World War II : Fighting, Witnessing, Remembering - Murav, Harriet; Estraikh, Gennady (Borderlines: Russian and East European-Jewish Studies, 2017)
This volume discusses the participation of Jews as soldiers, journalists, and propagandists in combating the Nazis during the Great Patriotic War, as the period between June 22, 1941, and May 9, 1945 was known in the Soviet Union. The essays included here examine both newly-discovered and previously-neglected oral testimony, poetry, cinema, diaries, memoirs, newspapers, and archives. This is one of the first books to combine the study of Russian and Yiddish materials, reflecting the nature of the Jewish Anti-Fascist Committee, which, for the first time during the Soviet period, included both Yiddish-language and Russian-language writers. This volume will be of use to scholars, teachers, students, and researchers working in Russian and Jewish history.